2005
DOI: 10.1128/jb.187.2.629-638.2005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MinD Mutations Reveals Residues Required for MinE Stimulation of the MinD ATPase and Residues Required for MinC Interaction

Abstract: The MinD ATPase is critical to the oscillation of the Min proteins, which limits formation of the Z ring to midcell. In the presence of ATP, MinD binds to the membrane and recruits MinC, forming a complex that can destabilize the cytokinetic Z ring. MinE, which is also recruited to the membrane by MinD, displaces MinC and stimulates the MinD ATPase, resulting in the oscillation of the Min proteins. In this study we have investigated the role of lysine 11, present in the deviant Walker A motif of MinD, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 40 publications
6
72
0
Order By: Relevance
“…The MinE-binding site on the MinD surface is located close to the nucleotide-binding site, and MinE competes directly for interaction with D152 with K11, one of two highly conserved lysines in the P-loop (a glycine-rich extended loop that forms part of the Walker A motif) (Zhou et al, 2005). Zhou and colleagues (Zhou et al, 2005) found that substitution of D152 in the highly conserved ␣-helix seven of MinD eliminated the interaction of MinD with MinE.…”
Section: Interactions Mediating the Formation Of A Min Protein Complementioning
confidence: 99%
See 1 more Smart Citation
“…The MinE-binding site on the MinD surface is located close to the nucleotide-binding site, and MinE competes directly for interaction with D152 with K11, one of two highly conserved lysines in the P-loop (a glycine-rich extended loop that forms part of the Walker A motif) (Zhou et al, 2005). Zhou and colleagues (Zhou et al, 2005) found that substitution of D152 in the highly conserved ␣-helix seven of MinD eliminated the interaction of MinD with MinE.…”
Section: Interactions Mediating the Formation Of A Min Protein Complementioning
confidence: 99%
“…The MinE-binding site on the MinD surface is located close to the nucleotide-binding site, and MinE competes directly for interaction with D152 with K11, one of two highly conserved lysines in the P-loop (a glycine-rich extended loop that forms part of the Walker A motif) (Zhou et al, 2005). Zhou and colleagues (Zhou et al, 2005) found that substitution of D152 in the highly conserved ␣-helix seven of MinD eliminated the interaction of MinD with MinE. Investigation of the effects of substituting the corresponding conserved residue in AtMinE1 (D213) had no affect on the interaction between AtMinD1 and AtMinE1 (data not shown), suggesting that the specific amino acids involved in the interaction of AtMinD1 with AtMinE1 might have changed.…”
Section: Interactions Mediating the Formation Of A Min Protein Complementioning
confidence: 99%
“…Zhou et al reported that conserved lysine residues (K11, K16) were necessary for formation of MinD dimmer. 14) However, roles of K11 and K16 residues in ATP-dependent dimerization of MinD have not been clear. In the present study, fluorescent polarization analysis indicates that the substitution of highly conserved lysine (K11, K16) to alanine does not affect to nucleotide binding affinity of MinD ATPase.…”
Section: (B) One To One Hundred Mole Equivalents Of Atp Was Added To mentioning
confidence: 99%
“…In the case of K11A and K16A, the amount of mutant protein in pellet fraction did not increase even in the presence of ATP or ATP-gS, indicating that loss of these lysine residues abolished the membrane binding ability of MinD, which is consistent with previous studies. 11,14,22) Monitoring of Fluorescently-Labeled ATP Binding to MinD by Fluorescence Polarization The fluorescent ATP analog MANT-ATP has been used to study the molecular mechanism of nucleotide binding proteins. [24][25][26] MANT-ATP can be used in a fluorescence polarization method that has been developed to monitor nucleotide binding to ATPase proteins.…”
mentioning
confidence: 99%
“…Second, we predict that MinE can only begin to transiently attach to the membrane independently of MinD when it is in the dimer form with the membrane binding domains at both N-terminals exposed. This is analogous to MinD, which must be in the dimer form for stable binding to the membrane (Zhou et al, 2005).…”
Section: Modeling the E-ringmentioning
confidence: 99%